The effect of an orally‐dosed Gynostemma pentaphyllum extract (ActivAMP®) on body composition in overweight, adult men and women: A double‐blind, randomised, placebo‐controlled study. Issue 3 (9th August 2021) - Rao, Amanda; Clayton, Paul; Briskey, David
Abstract: Background: The present study examined the effect of a herbal supplement containing a Gynostemma pentaphyllum (Gpp) extract (ActivAMP®) with respect to improving body composition in overweight males and females. Methods: One‐hundred and seventeen men and women aged over 18 years completed 16 weeks of daily supplementation with either Gpp or a placebo. Participants underwent dual‐energy X‐rays to assess body composition (fat mass, lean mass and mass distribution), as well as anthropometric measures (weight, height, hip and waist circumference), in addition to blood tests to assess inflammatory and safety markers. Results: Following 16 weeks of treatment, the Gpp group had a significant reduction in total body weight, body mass index, total fat mass and gynoid fat mass compared to the placebo group. Blood measures showed plasma triglyceride, alanine aminotransferase and tumour necrosis factor‐α to be statistically different between groups at week 16. Subgroup analysis of gender for fat distribution showed males in the Gpp group had a significant reduction in visceral fat compared to males in the placebo group and females in the Gpp group had a significant reduction in gynoid fat compared to the placebo group. Conclusions: Gpp was capable of altering fat mass and fat distribution in overweight and obese males and females compared to a placebo. Abstract : The therapeutic properties of Gynostemma pentaphyllum are proposed to be related to activation of AMP‐kinase and there is a growing body of evidence to support its use in weight loss. The results of this double‐blind randomised placebo‐controlled trial in overweight men and women indicate that supplementation with G. pentaphyllum over 16 weeks reduced body weight and fat mass.